Stigma and Perceptions of the Community Mental Health Implementation Team on Mental Health Problems in the Community - Fajar Rinawati; Novita Setyowati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The Community Mental Health Implementation Team or TP-KJM is a team at the District/City level which consists of several elements and is directly involved in mental health issues in the community. The purpose of this study was to provide an overview of the stigma and perceptions of the TP-KJM regarding mental health problems in the community. This research design is descriptive quantitative with cross sectional approach. The sample in this study were part of the TP-KJM, as many as 46 respondents. Data were collected using an instrument in the form of a questionnaire The results showed that 57% of the TP-KJM had a negative stigma and 43% had a positive stigma regarding mental health problems in the community. The description of negative stigma includes assuming that people with mental disorders (ODGJ) cannot control themselves (33%), cannot be allowed to do their own activities outside (26%), people who cannot take care of themselves (24%), are dangerous (22%), disturbing the peace in society (20%), unable to work normally (17%), have no future (4%), disgrace in the family and society (4%), and disturbs the safety of others and the environment (2%).